2008
DOI: 10.1002/ejoc.200701218
|View full text |Cite
|
Sign up to set email alerts
|

Chromium‐Thiophene‐salen‐Based Polymers for Heterogeneous Asymmetric Hetero‐Diels–Alder Reactions

Abstract: New chiral thiophene-salen ligands have been synthesized and the corresponding chromium complexes proved to be efficient catalysts for promoting asymmetric hetero-DielsAlder reactions with good activities and high enantioselectivities (up to 88 % ee). These complexes were successfully electropolymerized to give chiral polymers as insoluble powders for use in asymmetric heterogeneous catalysis. When engaged in successive hetero-Diels-Alder reactions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Indeed at each catalysts reuse, different targeted pyranones were obtained, in their pure form, without being contaminated by the presence of products traces synthesized during the previous catalytic cycle, with activities and enantioselectivities remaining very stable. [14] This study was continued to examine the extent of the chromium-containing thiophene-salen polymers application, and we were delighted to show their efficiency to promote the Henry reaction, even if the number of effective recycling remained lower than in the previous example. [15] The reaction occurred for instance between various alkyl or aryl aldehydes and nitromethane in the presence of substoichiometric amount of Hünig's base, and it produced the desired nitroaldols with enantiomeric excesses reaching up to 77 % (see scheme 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed at each catalysts reuse, different targeted pyranones were obtained, in their pure form, without being contaminated by the presence of products traces synthesized during the previous catalytic cycle, with activities and enantioselectivities remaining very stable. [14] This study was continued to examine the extent of the chromium-containing thiophene-salen polymers application, and we were delighted to show their efficiency to promote the Henry reaction, even if the number of effective recycling remained lower than in the previous example. [15] The reaction occurred for instance between various alkyl or aryl aldehydes and nitromethane in the presence of substoichiometric amount of Hünig's base, and it produced the desired nitroaldols with enantiomeric excesses reaching up to 77 % (see scheme 3).…”
Section: Methodsmentioning
confidence: 99%
“…These catalysts promoted the reaction with high efficiency and enantioselectivity, albeit with lower ee values compared to the best ones previously reported in the literature. [14] The thiophene withdrawing substituent in the fifth position of the salen replacing the donating tert-butyl group is probably slightly detrimental to the enantiofacial discrimination. Reactions were then successfully conducted under heterogeneous conditions with the polymers, and for instance successive HDA reactions were performed by using cyclohexanecarbaldehyde, affording the targeted product in high yield and enantioselectivity, showing no loss of efficiency for up to 15 cycles (see scheme 2).…”
Section: Salen-containing Polymers By Oxidative Polymerizationmentioning
confidence: 99%
“…In both cases, the catalyst immobilization proved to be a bit detrimental for the reaction enantioselectivity. The authors showed that despite some yield fl uctuation, this system was very robust and achieved a recyclability of 20 cycles in the cyclization reaction [154] .…”
Section: Salen -Type Ligandsmentioning
confidence: 99%
“…More recently, the electropolymerization of (thiophene-salen)chromium derivatives afforded recoverable chiral polymers immobilized onto inert surfaces that exhibit moderate enantioselectivity in hetero-Diels-Alder (HDA) reactions. [16] Thiophene-functionalized bipyridine ligands have been previously reported as potential precursors to polymeric heterogeneous catalysts; [17] however, attempts to electrochemically polymerize and co-polymerize these monomers were unsuccessful.…”
Section: Introductionmentioning
confidence: 99%